Abscisic acid-determined seed vigour differences do not influence redox regulation during ageing. Issue 6 (22nd March 2019) - Schausberger, Christina; Roach, Thomas; Stöggl, Wolfgang; Arc, Erwann; Finch-Savage, William E.; Kranner, Ilse
Abstract : High seed quality is a key trait to achieve successful crop establishment required for optimum yield and sustainable production. Seed storage conditions greatly impact two key seed quality traits; seed viability (ability to germinate and produce normal seedlings) and vigour (germination performance). Accumulated oxidative damage accompanies the loss of seed vigour and viability during ageing, indicating that redox control is key to longevity. Here, we studied the effects of controlled deterioration at 40°C and 75% relative humidity (RH) ('ageing') under two different O2 concentrations (21 and 78% O2 ) in Brassica oleracea . Two B. oleracea genotypes with allelic differences at two QTLs that result in differences in abscisic acid (ABA) signalling and seed vigour were compared. Ageing led to a similar loss in germination speed in both genotypes that was lost faster under elevated O2 . In both genotypes, an equal oxidative shift in the glutathione redox state and a minor loss of α-tocopherol progressively occurred before seed viability was lost. In contrast, ABA levels were not affected by ageing. In conclusion, both ABA signalling and seed ageing impact seed vigour but not necessarily through the same biochemical mechanisms.